Implementation of Law no. 2 of 2004 concerning the Settlement of Industrial Relations Disputes Amid the Covid-19 Pandemic in North Sulawesi Province - Ticoalu, Maya Geil Theresia Berlian; Kairupan, Sisca Beatrix; Mandagi, Marthinus (Technium Social Sciences Journal, 2021)
The COVID-19 outbreak at the beginning of 2020 shocked the world had a significant impact on the world community. The deadly virus, first discovered in Wuhan, China, killed thousands of people in various countries. Regulations or policies that the government has set are very influential in every sector and aspect of human life. Disputes or cases are possible in every human relationship. They were even considering that legal subjects have long known legal entities, the more parties involved in them. With the increasingly complex pattern of people’s lives, the scope of the incident or dispute event covers a broader scope, which often gets the spotlight on industrial relations disputes. The purpose of this article is industrial solution disputes, especially disputes through mediation dismissed in the middle of a pandemic covid 19 North Sulawesi as mandated by Article 8 of law No. 2 of 2004. The research was conducted using a qualitative approach. Researchers will use the data collection techniques to study the literature, field studies, observations, interviews, and documentation. The results of the study concluded; 1. The implementation of Law Number 2 the Year 2004 has been very effective in resolving disputes through the mediation process carried out by the Manpower and Transmigration Office of North Sulawesi Province. 2. There are still obstacles in the dispute resolution process through mediation conducted by the Manpower and Transmigration Office Transmigration of North Sulawesi Province, based on Law Number 1 of 2004. 3. There are several inhibiting factors in optimizing the settlement of industrial relations disputes in North Sulawesi. Such as companies that do not want to pay compensation on time, disputes after layoffs occur in the process of mediation. Dispute resolution time is more than the time limit by Law no. 2 of 2004. The implementation of dispute resolution is not by the procedure because the disputing parties are not